PERBANDINGAN JENIS KELAMIN (SEX RATIO) DAN PARAMETER PERTUMBUHAN IKAN SELUANG EKOR MERAH (Rasbora Lateristriata, Blkr 1854) DI WILAYAH HULU SUNGAI BARITO KALIMANTAN SELATAN, INDONESIA - Iriansyah Iriansyah; Erwin Rosadi; Isnaini Isnaini (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The purpose of this study is to analyze the biological parameters of the fish resources Seluang red tail (R. lateristriata) the fish sex ratio parameter (sex ratio) and the parameters of the population dynamics of the growth parameters of fish resources Seluang red tail (R. lateristriata) in the upstream region of the Barito River in South Kalimantan Indonesia. Methods of data collection are done by collecting samples at fish landing sites and fishing operations and held for 2 (two) months with a fixed time interval decision namely1 (one) week. The sex ratio of fish in the analysis by using chi-square analysis of the end.The growth parameters were analyzed fish-Walford Plot method, while theoretically Agefish when a width equal to 0 (t0) was performed using empirical equations Pauly (1984).The expected outcome of this research is the availability of scientific data related to thesex ratio comparison of fish and fish growth parameters Seluang red tail (R. lateristriata)in the upstream region of the Barito River in South Kalimantan. Comparison of the gender (sex ratio) Seluang fish red tail (R. lateristriata) of malesand females in the upstream region of the Barito River in South Kalimantan is 2: 1. Condition population dynamics parameters in the Barito river R. lateristriata South Kalimantan covering the theoretically maximum length parameter ( length infinity/108.15 mm, coefficient of growth (per unit time / K) of 0.350/ year, the parameters of thetheoretical age at the time of a length equal to zero (t0) of -0.14.